Simbolisme Dan Makna Dalam Ritual Suguh Sesaji Kesenian Jaranan Pegon Kyai Menggung Di Desa Mangunharjo Kecamatan Arjosari - Sintya, Ayu Kris; Hendriyanto, Agoes (LPPM Institut Pendidikan Nusantara Global, 2025)
The Suguh Sesaji ritual in the Jaranan Pegon Paguyuban Kyai Menggung performance plays an important role in strengthening the identity of the Mangunharjo community, Pacitan. Various elements of the offerings prepared in the Jaranan Pegon performance are believed to have a psychological influence on the performers, thus contributing to a performance that amazes the audience. This study aims to describe the symbolic meaning of the contents of the offerings used in the Suguh Sesaji ritual. This study uses a qualitative descriptive method with a semiotic approach. The results of the study show that the offerings in the Jaranan Pegon performance include various elements, such as incense, frankincense, seven types of flowers, salt, bitter coffee, ingkung chicken, cok bakal, Serimpi and Fanbo perfumes, yellow rice, glutinous rice, two combs of plantain, coconut, and kampung eggs. These elements have symbolic meanings that are passed down from generation to generation, such as delivering prayers, asking for safety, honoring ancestors, attracting sustenance, and keeping away bad things. The myth that developed stated that these offerings can bring spiritual powers, such as genies or spirits, which are believed to make the movements of the players more attractive and interesting. This study emphasizes the importance of understanding the symbolic meaning of offerings as an effort to preserve the Jaranan Pegon tradition and make it more interesting through the unique acrobatic movements of the players.